Sonochemical Microstructuring of Sodium Alginate to Increase its Effectiveness in Bakery - Anastasia V. Paymulina; Irina Yu. Potoroko; Natalia V. Naumenko; Oleg K. Motovilov (Техника и технология пищевых производств)
Algae are a source of many biologically active compounds that can be used in food production to expand the range of functional products. For instance, sodium alginate possesses a complex of scientifically proven biologically active properties. In the food industry, it usually serves as a thickener, stabilizer, gelatio n agent, and water-retaining agent. The biological activity of this polysaccharide and its effect on the technological properties of food systems depend on the molecular weight and particle size uniformity. The present research objective was to study the method of sonochemical microstructuring of sodium alginate to increase its biological activity and efficiency as part of v arious bakery formulations. The research featured alginate gels, yeast suspensions of Saccharomyces cerevisiae, and bakery products. The sonochemical microstructuring of sodium alginate involved a low-frequency ultrasonic treatment at 240, 435, and 630 W/L and 50°C for 20, 25, and 30 min. The effect of the treatment included the following indicators: particle morphology vs. distribution of the hydrodynamic particle diameter in a dispersed medium, antioxidant activity, dynamic viscosity, in vitro bioactivity, and bioavailability against Paramecium caudatum and S. cerevisiae. The quality assessment of bakery products followed State Standard 58233-2018. The process of sonochemical microstructuring depolymerized large particles of sodium alginate into shorter ones: 5670 nm – 30.6%, 502 nm – 53.4%, 56.1 nm – 16%. It increased the antioxidant activity by 7 times and the potential in vitro bioactivity by 3.9%. The microstructured sodium alginate improved the fermentation activity of S. cerevisiae and reduced the yeast biomass by 8%. The resulting bakery products had a greater porosity by 5.9% and antioxidant activity by 3.7 times. The sonochemical microstructuring reduced the particle size of sodium alginate, as well as increased its biological activity. The sonochemically microstructured sodium alginate demonstrated a great potential for baked foods.